Shariah Law and Economic Justice: Analyzing the Impact of Zakat on Income Distribution in Indonesia - Flores, Josefa; Santos, Luis; Tariq, Usman (Sharia Oikonomia Law Journal, 2025)
Zakat, one of the five pillars of Islam, is a mandatory form of almsgiving aimed at redistributing wealth and promoting economic justice. In Indonesia, the world’s largest Muslim-majority country, zakat has the potential to significantly impact income distribution and reduce poverty. However, its effectiveness is often hindered by inefficiencies in collection, distribution, and utilization. This study examines the impact of zakat on income distribution in Indonesia, focusing on its role in reducing economic inequality and promoting social welfare. The research aims to identify the challenges and opportunities associated with zakat management and propose strategies for enhancing its effectiveness. Using a mixed-methods approach, this study combines quantitative analysis of income distribution data with qualitative interviews with zakat institutions, beneficiaries, and policymakers. Data were analyzed to assess the impact of zakat on poverty alleviation, income inequality, and economic empowerment. The findings reveal that zakat has a modest but positive impact on income distribution, particularly in rural areas. However, inefficiencies in collection and distribution, as well as a lack of transparency, limit its potential to achieve broader economic justice. The study concludes that improving zakat management through better governance, transparency, and targeted distribution strategies is essential for maximizing its impact on income distribution. This research contributes to the discourse on Islamic economics by providing practical recommendations for enhancing the role of zakat in promoting economic justice and social welfare in Indonesia.